2023
DOI: 10.1029/2022gl102523
|View full text |Cite
|
Sign up to set email alerts
|

Electron Heating in Magnetosheath Turbulence: Dominant Role of the Parallel Electric Field Within Coherent Structures

Abstract: Energy cascade is one of the most prominent features of turbulence. Energy is injected at large scales, like fluid scales, then cascades to small scales through non-linear interactions, and finally dissipated at kinetic scales, leading to plasma heating and particle acceleration and the formation of suprathermal tails in the particle energy spectrum (Kiyani et al., 2015). Space plasma is typical of weak collisionality; hence collisionless mechanisms play a critical role in turbulent energy dissipation in space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The contribution by E || (Figure 6b) has a slight decreasing trend over time, where the median value is above 50% at the early time and below 50% later. The dominant role of E || energization is consistent with recent observations in magnetosheath turbulence where the pdf of the work done by E || to electrons is found (Xu et al, 2023), and kinetic simulations of turbulence where T e|| enhancements are found to be significant around the reconnection onset (Franci et al, 2022). For the decomposition of j e⊥ • E ⊥ , at the later time, the relative importance is consistent with the laminar reconnection studies (e.g., Dahlin et al, 2014Dahlin et al, , 2015Dahlin et al, , 2016Li et al, 2015Li et al, , 2017: the Fermi term (Figure 6c) dominates the positive contribution, and the Betatron term (Figure 6d) is negative.…”
Section: Electron Energizationsupporting
confidence: 90%
“…The contribution by E || (Figure 6b) has a slight decreasing trend over time, where the median value is above 50% at the early time and below 50% later. The dominant role of E || energization is consistent with recent observations in magnetosheath turbulence where the pdf of the work done by E || to electrons is found (Xu et al, 2023), and kinetic simulations of turbulence where T e|| enhancements are found to be significant around the reconnection onset (Franci et al, 2022). For the decomposition of j e⊥ • E ⊥ , at the later time, the relative importance is consistent with the laminar reconnection studies (e.g., Dahlin et al, 2014Dahlin et al, , 2015Dahlin et al, , 2016Li et al, 2015Li et al, , 2017: the Fermi term (Figure 6c) dominates the positive contribution, and the Betatron term (Figure 6d) is negative.…”
Section: Electron Energizationsupporting
confidence: 90%
“…Figure 3b exhibits the κ value of electrons with 1 keV energy, encompassing the energy range of most electrons (Ma et al, 2020;Xu et al, 2023). Throughout the entire interval, the κ value consistently exceeds 3, indicating that electrons satisfy the guiding center approximation within the three MFRs, allowing for the quantification of the power densities of the three acceleration mechanisms using Equations 1-3.…”
Section: 1029/2023ja032270mentioning
confidence: 96%
“…In principle, the first-order acceleration of a well-magnetized particle includes Fermi, betatron mechanism, and direct acceleration by parallel electric field (e.g., Northrop, 1963). The power densities of the first-order Fermi, betatron, and E || mechanism can be estimated using the following formulas (Akhavan-Tafti et al, 2019;Dahlin et al, 2014;Ma et al, 2020Ma et al, , 2022Xu et al, 2023;Zhong et al, 2020):…”
Section: 1029/2023ja032270mentioning
confidence: 99%
“…Retino et al (2007) reported the first reconnection event in the magnetosheath with Cluster observations, where an ion diffusion region is identified, and they proposed that magnetic reconnection occurs in the current sheet formed due to plasma turbulence. More reconnection events have recently been observed with the high-resolution measurements provided by the Magnetospheric Multiscale spacecraft, and the width of the associated current sheets ranges from the ion kinetic scale to the electron kinetic scale (Yordanova et al 2016;Vörös et al 2017;Phan et al 2018;Gingell et al 2019Gingell et al , 2020Stawarz et al 2019;Wang et al , 2021Xu et al 2023). Most of these reconnection events have been observed downstream of a quasi-parallel shock, which indicates that magnetic reconnection may occur ubiquitously in the quasi-parallel-shocked magnetosheath.…”
Section: Introductionmentioning
confidence: 98%